PENGARUH USIA, JENIS KELAMIN DAN INTENSITAS BERMAIN GAME ONLINE TERHADAP KELELAHAN FISIK REMAJA DI MASA PANDEMI COVID-19 DI DESA TALOK KECAMATAN KRESEK TANGERANG - Oka Hardiansya; Eka Noviana Nasriyanto (Nusantara Hasana Journal, 2022)
Online games or online games are games that are played over a network (LAN or internet). Purpose to find out about the effect of online games on adolescent physical fatigue during the covid-19 pandemic. Research using descriptive analytic whose aim is to find the relationship between variables. Sampling can be formulated using the Slovin formula as follows. Data analysis using univariate and bivariate analysis. Analysis of the intensity of playing online games with complaints of physical fatigue showed that there were 31 (86.1%) high intensity of playing online games experiencing fatigue. While the intensity of playing online games is moderate who experience fatigue as many as 20 (71.4%). And the intensity of playing online games is low and there is no fatigue (0%). The results of the Chi Square test obtained p value = 0.001 so it can be concluded that there is a difference in the proportion of incidents of high, medium and low intensity of playing online games.